A New Stochastic Model to Find the Insulin Secretion from Human Islets Using Exponential Distribution - Kumar, P. Senthil; Balasubramanian, K.; Kumar, A. Dinesh (IJRDO -JOURNAL OF MATHEMATICS, 2015)
Many plant based products have been suggested as potential antidiabetic agents, but few have been shown to be effective in treating the symptoms of Type 2 diabetes mellitus (T2DM) in human studies, and little is known of their mechanisms of action. The effects of a novel high molecular weight Gymnema sylvestre (GS) extract, Om Santal Adivasi (OSA) on plasma insulin, C-peptide and glucose in a small cohort of patients with T2DM are reported here. Oral administrationof OSA induced significant increases in circulating insulin and Cpeptide, which were associated with significant reductions in fasting and post-prandial blood glucose. The results of insulin secretion from human islets of langerhans were compared using the marginal distribution of a stretched Brownian motion